Incidence and significance of findings on spinal MRIs in a paediatric population with spinal column complaints. (February 2021) - Rathjen, Karl; Dieckmann, Rebecca J.; Thornberg, David C.; Karam, AnnMarie; Birch, John G.
Abstract: Purpose: We sought to identify correlations between working diagnosis, surgeon indication for obtaining spinal MRI and positive MRI findings in paediatric patients presenting with spinal disorders or complaints. Methods: Surgeons recorded their primary indication for ordering a spinal MRI in 385 consecutive patients. We compared radiologist-reported positive MRI findings with surgeon response, indication, working diagnosis and patient demographics. Results: The most common surgeon-stated indications were pain (70) and coronal curve characteristics (63). Radiologists reported 137 (36%) normal and 248 (64%) abnormal MRIs. In total, 58% of abnormal reports (145) did not elicit a therapeutic or investigative response, which we characterized as 'clinically inconsequential'. In all, 42 of 268 (16%) presumed idiopathic scoliosis patients had intradural pathology noted on MRI. Younger age (10.3 years versus 12.0 years) was the only significant demographic difference between patients with or without intradural pathology. Surgeon indication 'curve magnitude at presentation' was associated with intradural abnormality identification. However, average Cobb angles between patients with or without an intradural abnormality was not significantly different (39° versus 37°, respectively). Back pain without neurological signs or symptoms was a negative predictor of intradural pathology. Conclusion: Radiologists reported a high frequency of abnormalities on MRI (64%), but 58% of those were deemed clinically inconsequential. Patients with MRI abnormalities were two years' younger than those with a normal or inconsequential MRI. 'Curve magnitude at presentation' in presumed idiopathic scoliosis patients was the only predictor of intrathecal pathology. 'Pain' was the only indication significantly associated with clinically inconsequential findings on MRI. Level of evidence: III